Exosome-mediated ferroptosis in the tumor microenvironment: from molecular mechanisms to clinical application - Na Liu; Tianqing Wu; Guohu Han; Minbin Chen (Cell Death Discovery)
Abstract Ferroptosis in the tumor microenvironment (TME) plays a crucial role in the development, metastasis, immune escape, and drug resistance of various types of cancer. A better understanding of ferroptosis in the TME could illuminate novel aspects of this process and promote the development of targeted therapies. Compelling evidence indicates that exosomes are key mediators in regulating the TME. In this respect, it is now understood that exosomes can deliver biologically functional molecules to recipient cells, influencing cancer progression by reprogramming the metabolism of cancer cells and their surrounding stromal cells through ferroptosis. In this review, we focus on the role of exosomes in the TME and describe how they contribute to tumor reprogramming, immunosuppression, and the formation of pre-metastatic niches through ferroptosis. In addition, we highlight exosome-mediated ferroptosis as a potential target for cancer therapy and discuss strategies employing exosomes in ferroptosis treatment. Finally, we outline the current applications and challenges of targeted exosome-mediated ferroptosis therapy in tumor immunotherapy and chemotherapy. Our aim is to advance research on the link between exosomes and ferroptosis in the TME, and we pose questions to guide future studies in this area.